Speech Errors Produced by EFL Learners of Islamic Boarding School in Telling English Story - Utami, Agustina Ridho; Malihah, Noor (OKARA: Jurnal Bahasa dan Sastra, 2018)
The students of Islamic Boarding School Nurul Islam are used to learn spoken English, but they still make some errors when they are speaking. They often produce some speech errors when they are making an English conversation or when they are getting turn to speak in front of the class. This study aims to investigate the existence and the frequency of speech errors especially Silent Pause and Filled Pause produced by the students of Islamic Boarding School Nurul Islam in telling English Story. This research is a descriptive-qualitative with data presented in statistical forms. The object of this research is Speech Errors produced by students in telling English Story. And the respondents are 30 students from the 8th grade of English Tutorial Program in Islamic Boarding School Nurul Islam in the academic year of 2016/2017. This research was conducted by observation. It was to investigate the existence of Silent Pause and Filled Pause produced by the students in telling English story and to investigate the percentages of each speech errors. The findings of the observation in this research show 603 (100%) speech errors produced by students. Silent pause is 524 (87%) and Filled Pause is 79 (13%).Â Â 